COVID-19 and cardiac arrest: what we need to know - Saurabh Kumar; Abhilash Ludhiadch; Shiv Kumar Giri (The Egyptian Journal of Internal Medicine)
Abstract The coronavirus disease (COVID-19), which is an infectious respiratory illness, has severely impacted human health and data reports more than 7 million deaths to date. Although it is a respiratory illness, its association with several cardiac issues has been the primary area of research. Cardiac arrest is a major concern for SARS-CoV-2-infected patients or makes them more vulnerable to it. Multiple mechanisms (both direct and indirect) for increased cardiac arrest have been proposed. Studies have reported that multiorgan failure has a significant impact on infected patients. Multifactorial risk involvement is responsible for the increased incidence of cardiac arrests. Therefore, it is crucial to understand how SARS-CoV-2 affects the heart.